2021
DOI: 10.1097/md.0000000000025240
|View full text |Cite
|
Sign up to set email alerts
|

Staged vs simultaneous bilateral unicompartmental knee arthroplasty for clinical outcomes

Abstract: Background: Bilateral unicompartmental knee arthroplasty (UKA) can be divided into one or two stages clinically. Compared with staged bilateral UKA, whether simultaneous bilateral UKA has better clinical efficacy remains to be verified. Methods: PubMed, EBSCO, and Web of Science were searched by us for meta-analysis. Studies were considered eligible for inclusion if they included simultaneous and staged UKA. We excluded studies unrelated to the research question, studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
6
1
1
Order By: Relevance
“…Al igual que en otros estudios, creemos que con una adecuada selección de los pacientes no aumenta el riesgo de complicaciones ni se retrasa la rehabilitación en los pacientes operados en un tiempo. 26 Los que se operaron secuencial lo hicieron así porque la segunda rodilla operada presentó síntomas como para requerir la intervención con posterioridad.…”
Section: Resultados Latinoamericanosunclassified
“…Al igual que en otros estudios, creemos que con una adecuada selección de los pacientes no aumenta el riesgo de complicaciones ni se retrasa la rehabilitación en los pacientes operados en un tiempo. 26 Los que se operaron secuencial lo hicieron así porque la segunda rodilla operada presentó síntomas como para requerir la intervención con posterioridad.…”
Section: Resultados Latinoamericanosunclassified
“…Many studies have found no difference in postoperative functional outcomes between patients with simultaneous and staged UKA. 3 4) In their meta-analysis, Chen et al 18) found no significant difference in postoperative OKS between the simultaneous and staged groups. The median change in VAS scores at the end of the first year in the present study was 6 in the simultaneous group and 5 in the staged group.…”
Section: Discussionmentioning
confidence: 97%
“… 15 16) A couple of previous studies have compared staged and simultaneous bilateral UKA, but these studies have mainly focused on cemented implants. 17 18) …”
mentioning
confidence: 99%
“…There is moderate evidence to suggest equivalent improvement in functional outcomes 27 . Similarly, in a systematic review of 8 studies, simultaneous bilateral UKA was shown to effectively reduce the operative time, length of stay, and hospital cost without increasing postoperative complications compared with staged bilateral UKA 28 . Given the different risk-benefit profiles of the 2 procedures, these potential complications must be interpreted for each patient individually.…”
Section: Bilateral Taa Literaturementioning
confidence: 91%